Lou [videorecording (DVD)] - Chayko, Belinda; Hurt, John, 1940-2017; Barclay, Emily, 1984-; Tindley, Lily Bell; Farinacci, Daniella (Monarch Home Video, 2011)
Not long after eleven-year-old Lou's father walks out of her life, her irascible and befuddled grandfather crashes in. But when Doyle comes to stay, Lou discovers, against all her expectations, the healing power of love.